A snippet from neXtSIM_DG : next generation sea-ice model with DG ... - Richter, Thomas; Dansereau, Véronique; Lessig, Christian; Minakowski, Piotr (Zenodo, 2023)
A snippet from neXtSIM_DG : next generation sea-ice model with DG This archive contains the software described and required to reproduce the numerical results of the manuscript "The neXtSIM-DG dynamical core: A Framework for Higher-order Finite Element Sea Ice Modeling" by Thomas Richter, Véronique Dansereau, Christian Lessig and Piotr Minakowski. We strongly recommend that you access nextsim-DG's GitHub page https://github.com/nextsimdg/nextsimdg instead of this archive for the latest version of the code. The software is still under active development and this excerpt contains only a very small part of it. In the present form, it is provided for self-contained reproducibility. neXtSIM-DG is created as part of SASIP: The Scale-Aware Sea Ice Project which is funded by Schmidt Futures, a philanthropic initiative founded by Eric and Wendy Schmidt that bets early on exceptional people making the world better, particularly through innovative breakthroughs in science and technology. It is a project of Schmidt ...